(untitled) (Physical Education, Health and Social Sciences, 2025)
This study examines the extensive infrastructural reforms launched during Shahbaz Sharif’s decade-long governance in Punjab. This study highlights how previously neglected school environments lacking water, electricity, latrines, safety, and accessibility were transformed through targeted planning, mapping, and reconstruction. It analyzes the transition towards climate-sensitive architectural standards, child-friendly facilities, inclusive needs (such as ramps), upgraded boundary walls, and appealing improvement initiatives. This article determines how the Punjab School Education Plan (2013-2017) and the School Reforms Roadmap served as catalysts in reducing public-private disparities, uplifting rural areas schooling conditions and increasing student satisfaction. By exploring both quantitative indicators and qualitative improvements, also this study argues that infrastructure has become the backbone of Punjab’s educational resurgence, establishing a secure and comprehensive learning environment across the Punjab province.